Roles of Traditional and Next-Generation Probiotics on Non-Alcoholic Fatty Liver Disease (NAFLD) and Non-Alcoholic Steatohepatitis (NASH): A Systematic Review and Network Meta-Analysis - Zhu, Yuezhi; Tan, Jen Kit; Liu, Jia; Goon, Jo Aan (Antioxidants, 2024)
Non-alcoholic fatty liver disease (NAFLD) and its progressive stage, non-alcoholic steatohepatitis (NASH), are becoming one of the most common chronic liver diseases globally. Lifestyle interventions such as weight reduction, increased physical activity, and maintaining healthy diets play a pivotal role in managing NAFLD/NASH. Recent studies suggest that the gut microbiome is associated with the pathogenesis of NAFLD/NASH, prompting microbiome-targeted therapy to emerge as a new therapeutic option for NAFLD/NASH. We conducted a systematic review based on the PRISMA statement and employed network meta-analysis to investigate the effects of traditional probiotics and next-generation probiotics (NGPs) on NAFLD/NASH. Comparative analysis reveals that traditional probiotics primarily reduce liver fat deposition and inflammation by improving gut microbiota composition, enhancing intestinal barrier function, and modulating immune responses. In contrast, NGPs demonstrate a more significant therapeutic potential, attributed to their direct effects on inhibiting oxidative stress and their ability to enhance the production of short-chain fatty acids (SCFAs), NGPs appear as a new potential strategy for the management of NAFLD/NASH through their dual action of directly inhibiting oxidative stress and enhancing SCFA production, highlighting the importance of understanding and utilizing the direct and indirect regulatory mechanisms of oxidative stress in the management of NAFLD/NASH.